Role of F-box WD Repeat Domain Containing 7 in Type 1 Diabetes - Mohammed, Sarah W.; Qassam, Zainab M.; Taha, Ekhlass M.; Salih, Nameer M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Type I diabetes (T1DM) is a chronic immune system disease characterized by the devastation or injury of ß-cells in the Langerhans Island, resulting in insulin deficiency and hyperglycemia. This study determines the new marker F-box and WD repeat domain containing 7 (FBXW7). One hundred twenty type 1 diabetic patients from three different places (central child hospital, Alkindi center for diabetes and endocrinology, Children’s Education Hospital) in Iraq during the period from (20 December 2021 to 25 March 2022) an age ranges of (4-17) years. The patient group consisted of being derived to three groups: group one healthy patient group (33) was included as healthy patient, group two (20) newly diagnosed T1DM and (67) type 1 diabetic with insulin treatment. The quantitative enzyme-linked immunosorbent assay (ELISA) biochemical parameters were used to quantify the protein FBXW-7 levels. FBG, Cholesterol, Triglyceride, HDL, LDL, VLDL, HbA1c, GOT, GPT, Total Oxidant status, and Total Antioxidant status were measured through spectrophotometry. Serum FBXW-7 protein levels were considerably elevated noticeably (p-value = 0.00). In terms of FBXW7 protein, there was a significant variation between the new and therapy groups. There was no significant variation in protein levels between the new compared to healthy groups. Serum FBXW-7 protein was positively correlated with FBG, TG, cholesterol, GOT, GPT, LDL, and VLDL, and was negatively correlated with HDL in the patient group. According to ROC analysis, the cutoff value for FBXW-7 protein was (1.9) in the newly group and (2.1) in the treatment group. Levels of FBXW-7 protein are elevated in DM patients. FBXW-7 protein was significantly different in the treatment group but not different in the newly group when compared with the healthy group.